2021
DOI: 10.1155/2021/6637513
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Human Follicle Dermal Papilla Cells in response to Porphyra-334 Treatment by RNA-Seq

Abstract: Porphyra-334 is a kind of mycosporine-like amino acid absorbing ultraviolet-A. Here, we characterized porphyra-334 as a potential antiaging agent. An in vitro assay revealed that porphyra-334 dramatically promoted collagen synthesis in fibroblast cells. The effect of porphyra-334 on cell proliferation was dependent on the cell type, and the increase of cell viability by porphyra-334 was the highest in keratinocyte cells among the three tested cell types. An in vivo clinical test with 22 participants demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
3
0
1
Order By: Relevance
“…Um teste clínico in vivo com 22 participantes demonstrou o possível papel da porphyra-334 na melhora das rugas periorbitais. Descobriu-se que vários genes associados com o ciclo do folículo piloso, a estrutura do folículo piloso, a estrutura epidérmica e as células-tronco foram reguladas positivamente pelo tratamento da porphyra-334, sugerindo o papel potencial da porphyra-334 no crescimento e manutenção do folículo piloso (Kim et al, 2021).…”
Section: Compostos De Origem Marinhaunclassified
“…Um teste clínico in vivo com 22 participantes demonstrou o possível papel da porphyra-334 na melhora das rugas periorbitais. Descobriu-se que vários genes associados com o ciclo do folículo piloso, a estrutura do folículo piloso, a estrutura epidérmica e as células-tronco foram reguladas positivamente pelo tratamento da porphyra-334, sugerindo o papel potencial da porphyra-334 no crescimento e manutenção do folículo piloso (Kim et al, 2021).…”
Section: Compostos De Origem Marinhaunclassified
“…It has been observed that UVR potently inhibits the expression of genes encoding elastin and procollagen C-endopeptidase (PCOLCE). To explore the anti-aging properties of porphyra-334 and shinorine, Kim et al [ 146 ] used human fibroblasts cells, HaCaT cells, and HFDP cells from normal human scalp hair follicles. Their findings demonstrated an improvement of periorbital wrinkles, promotion of collagen formation, and stimulation of cell reproduction.…”
Section: Functions Of Maasmentioning
confidence: 99%
“…MAAs possess multiple roles to aid against environmental stress conditions such as osmotic regulation, desiccation, control reproduction, nitrogen reservoir, thermal and salt stresses and toxicity by heavy metals [22,23,82,83]. MAAs from red seaweeds are reported as versatile metabolites with multiple functions including antioxidant, anti-inflammatory, antiaging, anticancer, and wound healing properties [63,[84][85][86]. Investigation of porphyra-334 isolated from Porphyra yezoensis exhibited a protective effect on human skin fibroblasts against exposure to UV-A radiation by increasing cell viability up to 88%.…”
Section: Photoprotectantmentioning
confidence: 99%